2012
DOI: 10.1002/mrc.2863
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical behavior of 77Se‐1H spin‐spin coupling constants in pyrazolyl‐1,3‐diselenanes and 1,2‐diselenolane

Abstract: Conformational study of five derivatives of 2‐(pyrazol‐4‐yl)‐1,3‐diselenane together with related 1,2‐diselenolane in respect to the stereochemical trends of geminal and vicinal 77Se‐1H spin‐spin coupling constants has been carried out by means of high‐level theoretical calculations in combination with experiment. The marked dihedral angle dependences for both types of couplings accounted for the lone pair effect in the case of geminal coupling constants and the Karplus‐type relationship for vicinal couplings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…In the earlier publications, the LDBS scheme was successfully applied for the calculation of chemical shieldings (chemical shifts) at the Hartree–Fock and DFT levels in a number of simple benchmark molecules, in relatively large molecular systems, and even in the model forms of biological molecules such as simple dipeptides . Different LDBS schemes were also systematically used for the calculation of NMR parameters at the DFT and nonempirical levels of theory in a number of more recent publications by Rusakov and coworkers together with numerous related publications not cited herewith in view of their multiplicity.…”
Section: Theoretical Methods and Accuracy Factorsmentioning
confidence: 99%
“…In the earlier publications, the LDBS scheme was successfully applied for the calculation of chemical shieldings (chemical shifts) at the Hartree–Fock and DFT levels in a number of simple benchmark molecules, in relatively large molecular systems, and even in the model forms of biological molecules such as simple dipeptides . Different LDBS schemes were also systematically used for the calculation of NMR parameters at the DFT and nonempirical levels of theory in a number of more recent publications by Rusakov and coworkers together with numerous related publications not cited herewith in view of their multiplicity.…”
Section: Theoretical Methods and Accuracy Factorsmentioning
confidence: 99%
“…There seems to be a tendency for the J value to follow the dihedral angle. It has been reported that 2 J (Se, H) is strongly dependent on the orientation of the selenium lone pair and 3 J (Se, H) follows classical Karplus‐type equation from experimental and theoretical approaches . 2 J (Se, C) have not been studied intensively and little is known about 3 J (Se, C) values .…”
Section: Resultsmentioning
confidence: 85%
“…The spin coupling constants of the seleno‐carbohydrates used in this study allow the following observations: J ( 77 Se, 13 C) value is explained by the hybrid orbital state, and the surrounding electron density seems to affect the value. 2 J ( 77 Se, 1 H) are greatly influenced by the dihedral angle formed with the selenium lone pair . Information on 2 J ( 77 Se, 13 C) is lacking thus preventing general conclusions. 3 J ( 77 Se, 1 H) values are for the most part explained by the Karplus relation . However, there are exceptions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental measurements of 2 J (Se,H) are performed using the low‐power CPMG‐HSQMBC technique, as described in our previous publications, whereas all calculations of 77 Se‐ 1 H couplings are carried out within a general second order polarization propagator approach (SOPPA), which recently has been extensively used for the high‐level calculations of different types of spin‐spin coupling constants – in a large number of saturated carbocycles, nitrogen‐containing heterocycles, functional derivatives of aldehydes and ketones, cyclic and open‐chain nitrogen‐containing compounds, fluorobenzenes, organic phosphines and phosphine chalcogenides . In particular, 77 Se‐ 1 H couplings were calculated in very good agreement with experiment in selanylalkenes, as well as in five‐membered and six‐membered selenium‐containing heterocycles – selenophenes, diselenanes and diselenolanes, derivatives of thiaselenetane, selenasilole, thiaselenole, thiaselenolane and dihydrothiaselenine, as well as in three representative selenoglycosides . a…”
Section: Introductionmentioning
confidence: 99%